(untitled) (Revista Contexto & Educação, 2024)
Health Education prioritizes the development of autonomous subjects who are aware of their collective and individual responsibilities in everyday decision-making, which will lead to healthy choices and, consequently, a better quality of life. In this aspect, inquiry-based teaching is a relevant approach in health education, because it promotes the development of life skills. The objective of this study lies in the analysis of the manifestation of investigative cognitive skills, namely in the emission of hypotheses and elaboration of conclusions, in students of the seventh year of a public school in Brazil, when participating in an investigative didactic sequence for health education. In this study, five elementary school students participated in three meetings. In our analysis, we found that students throughout the meetings developed skills to issue hypotheses and draw conclusions. Despite the limitations of the study, the results found show the potential that investigative didactic sequences in health education can have in the development of students’ cognitive skills and in their training to solve problems related to the promotion of their individual health and/or health. of your community.